THE INFLUENCE OF INTERNAL AND EXTERNAL FACTORS ON SHARIA BANKING FINANCING IN THE CITY OF BANDA ACEH - Nufus, Hayatun; Fitri, Aulia (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Factors that are thought to influence the amount of financing disbursed by Islamic banking are Non-Performing Financing (NPF), capital adequacy ratio (CAR), and Financing to Deposit Ratio (FDR). Economic conditions can be used as one of the external factors that can influence bank financing. One of the macro indicators is inflation. Especially in Banda Aceh, the GRDP for 2021 will reach Rp. 19 million. So seeing the relatively large nominal Islamic bank financing  a good impact on the economy in each region as described by GRDP. This study aims to determine (1) the short-term effect of internal factors (NPF, FDR, CAR) on Islamic banking financing in Banda Aceh City. (2) the short-term effect of external factors (inflation, GRDP) on sharia banking financing in Banda Aceh City. (3) the long-term influence of internal factors (NPF, FDR, CAR) on Islamic banking financing in Banda Aceh City. (4) the long-term influence of external factors (inflation, GRDP) on sharia banking financing in Banda Aceh City. The approach used in this research is quantitative. The population used in this study is Islamic banking in the City of Banda Aceh with samples taken from monthly data for 2017-2021. The sampling technique in this study was purposive sampling. Data analysis used the Vector Error Correction Model (VECM) through the Eviews 9 program. The results of the study show that the effect of the NPF, CAR, and FDR variables on bank financing in the short term has a positive but not significant impact. The influence of the inflation variable on financing in the short term has a positive but not significant impact. While GRDP has a negative impact but not a significant. The NPF and FDR variables have a positive and significant effect on bank financing, while the CAR variable has a positive but not significant effect in the long term. Inflation variable, GRDP has a positive and significant impact on sharia financing in the long term